Berkah ke Meja Kerja: Implementasi Nilai Aswaja dalam Profesionalisme Kantor - Fatkhullah, Faiz Karim; Canintika, Anissa Feby; Kembaren, Jefry Sondang; Hermansyah, Nerissa Arviana Koesuma (Universitas Respati Indonesia, 2026)
Rapid social and professional developments often create a gap between spiritual life and daily workplace practices, which can lead to the marginalization of religious values within professional environments. In Islamic teachings, work is not only viewed as a means of fulfilling material needs but can also be considered an act of worship when it is carried out with sincere intentions and guided by ethical principles. This article aims to examine the implementation of Ahlussunnah wal Jama’ah (Aswaja) values in fostering professionalism in office-based work settings. The study employs a literature review method by analyzing relevant academic sources discussing the core principles of Aswaja, including tasamuh (tolerance), tawazun (balance), tawasuth (moderation), i’tidal (justice), and amar ma’ruf nahi munkar (promoting good and preventing wrongdoing). The findings indicate that Aswaja values extend beyond ritual religious practices and function as a comprehensive ethical framework applicable to professional life. Tasamuh encourages mutual respect and inclusivity in the workplace, while tawazun emphasizes the importance of balancing worldly responsibilities with spiritual obligations. Furthermore, tawasuth guides moderate and balanced decision-making, and i’tidal reinforces fairness and integrity in professional conduct. Amar ma’ruf nahi munkar also serves as a moral foundation for maintaining ethical behavior and preventing misconduct. Integrating these values can help professionals develop responsible, ethical, and inclusive work attitudes, leading to success that encompasses not only material achievement but also moral integrity and spiritual well-being